Crucial factors determining colonisation patterns of bird species on oceanic islands in the Anthropocene - Daichi Iijima; Haruko Ando; Tohki Inoue; Takeshi Osawa; Nozomu J. Sato (Community Ecology, 2026)

Consensus Paper: Models of Cerebellar Functions - Shinji Kakei; Andreea C. Bostan; Timothy J. Ebner; Mohammad Amin Fakharian; Hiroaki Gomi; Xavier Guell; Marie Hemelt; Huu Hoang; Court Hull; Masato Inoue; Takahiro Ishikawa; Masashi Kameda; et al. (The Cerebellum, 2026)

Genetic evidence reveals that two wild boar (Sus scrofa) lineages invaded an island in Japan by swimming - Shintaro Ishizuka; Eiji Inoue; Takeo Kuriyama; Jun J. Sato (European Journal of Wildlife Research, 2025)

Hybridization and reticulate evolution in Diphasiastrum (flat-branched clubmosses, Lycopodiaceae) – New data from the island of Taiwan and Vietnam - M. Schnittler; M. Inoue; O.N. Shchepin; J. Fuchs; H. Chang; P. Lamkowski; R. Knapp; K. Horn; H.W. Bennert; M. Bog (Molecular Phylogenetics and Evolution, 2024)

Didymodon schensianus (Pottiaceae, Bryophyta), a new combination for a widespread, but overlooked taxon in East Asia - Juan A. Jiménez; María J. Cano; Yuya Inoue (Plant Biosystems, 2024)

Per- and polyfluoroalkyl substances and sleep health in U.S. adults, NHANES 2005–2014 - Pengfei Guo; Zhihao Jin; Giselle Bellia; Jiajun Luo; Kosuke Inoue; Krystal J. Godri Pollitt; Nicole C. Deziel; Zeyan Liew (Environmental Research, 2023)

Therapeutic angiogenesis for patients with no-option critical limb ischemia by adipose-derived regenerative cells: TACT-ADRC multicenter trial - Yuuki Shimizu; Kazuhisa Kondo; Ryo Hayashida; Ken-ichiro Sasaki; Masanori Ohtsuka; Yoshihiro Fukumoto; Shinichiro Takashima; Oto Inoue; Soichiro Usui; Masayuki Takamura; Masashi Sakuma; Teruo Inoue; et al. (Angiogenesis, 2022)

Distribution of vasopressin 1a and oxytocin receptor protein and mRNA in the basal forebrain and midbrain of the spiny mouse (Acomys cahirinus) - Jeanne M. Powell; Kiyoshi Inoue; Kelly J. Wallace; Ashley W. Seifert; Larry J. Young; Aubrey M. Kelly (Brain Structure and Function, 2022)

Distribution of brain oxytocin and vasopressin V1a receptors in chimpanzees (Pan troglodytes): comparison with humans and other primate species - Christina N. Rogers Flattery; Daniel J. Coppeto; Kiyoshi Inoue; James K. Rilling; Todd M. Preuss; Larry J. Young (Brain Structure and Function, 2022)

Microsatellite records for volume 13, issue 4 - Rachawadee Chantra; Yufei Dai; Miho Inoue-Murayama; Kongkiat Kittiwattanawong; Qi Luan Lim; Jeffrine J. Rovie-Ryan; Watchara Sakornwimon; Xianyan Wang; Liyuan Zhao (Conservation Genetics Resources, 2021)

New microsatellite markers for Ellipse, Venustaconcha ellipsiformis (Bivalvia: Unionidae), with notes on optimal sample size and cross-species amplification - Kentaro Inoue; Bernard E. Sietman; Stephen E. McMurray; J. Scott Faiman; David T. Zanatta (Molecular Biology Reports, 2021)

Enhanced vertical turbulent nitrate flux in the intermediate layer of the Kuroshio in the Tokara Strait - T. Tanaka; D. Hasegawa; I. Yasuda; D. Yanagimoto; S. Fujio; H. Nakamura; R. Inoue; J. Nishioka (Journal of Oceanography, 2021)

Cell-Permeable Calpain Inhibitor SJA6017 Provides Functional Protection to Spinal Motoneurons Exposed to MPP+ - Supriti Samantaray; Varduhi H. Knaryan; Angelo M. Del Re; John J. Woodward; Donald C. Shields; Mitsuyoshi Azuma; Jun Inoue; Swapan K. Ray; Naren L. Banik (Neurotoxicity Research, 2020)

Enrichment and characterization of a bacterial mixture capable of utilizing C-mannosyl tryptophan as a carbon source - Tanim J. Hossain; Shino Manabe; Yukishige Ito; Toshiya Iida; Saori Kosono; Kenji Ueda; Akira Hosomi; Daishi Inoue; Tadashi Suzuki (Glycoconjugate Journal, 2018)

Characterization of tomato leaf curl purple vein virus, a new monopartite New World begomovirus infecting tomato in Northeast Brazil - M. A. Macedo; L. C. Albuquerque; M. R. Maliano; J. O. Souza; M. R. Rojas; A. K. Inoue-Nagata; R. L. Gilbertson (Archives of Virology, 2018)

Vulnerability of Community-Based Forest Management to Climate Variability and Extremes: Emerging Insights on the Contribution of REDD+ - Rose Jane J. Peras; Juan M. Pulhin; Makoto Inoue (Small-scale Forestry, 2017)

Genes, social transmission, but not maternal effects influence responses of wild Japanese macaques (Macaca fuscata) to novel-object and novel-food tests - Coline M. Arnaud; Takafumi Suzumura; Eiji Inoue; Mark J. Adams; Alexander Weiss; Miho Inoue-Murayama (Primates, 2017)

Predicting the effects of climate change on population connectivity and genetic diversity of an imperiled freshwater mussel, Cumberlandia monodonta (Bivalvia: Margaritiferidae), in riverine systems - Kentaro Inoue; David J. Berg (Global Change Biology, 2017)
In the face of global climate change, organisms may respond to temperature increases by shifting their ranges poleward or to higher altitudes. However, the direction of range shifts in riverine systems is less clear. Because rivers are dendritic networks, there is only one dispersal route from any given location to another. Thus, range shifts are only possible if branches are connected by suitable habitat, and stream‐dwelling organisms can disperse through these branches. We used Cumberlandia monodonta (Bivalvia: Unionoida: Margaritiferidae) as a model species to investigate the effects of climate change on population connectivity because a majority of contemporary populations are panmictic. We combined ecological niche models ( ENM s) with population genetic simulations to investigate the effects of climate change on population connectivity and genetic diversity of C. monodonta . The ENM s were constructed using bioclimatic and landscape data to project shifts in suitable habitat under future climate scenarios. We then used forward‐time simulations to project potential changes in genetic diversity and population connectivity based on these range shifts. ENM results under current conditions indicated long stretches of highly suitable habitat in rivers where C. monodonta persists; populations in the upper Mississippi River remain connected by suitable habitat that does not impede gene flow. Future climate scenarios projected northward and headwater‐ward range contraction and drastic declines in habitat suitability for most extant populations throughout the Mississippi River Basin. Simulations indicated that climate change would greatly reduce genetic diversity and connectivity across populations. Results suggest that a single, large population of C. monodonta will become further fragmented into smaller populations, each of which will be isolated and begin to differentiate genetically. Because C. monodonta is a widely distributed species and purely aquatic, our results suggest that persistence and connectivity of stream‐dwelling organisms will be significantly altered in response to future climate change.

Simultaneous spawning by female stream goby Rhinogobius sp. and the association with brood cannibalism by nesting males - S. Ito; H. Iwao; J. Sakata; M. Inoue; K. Omori; Y. Yanagisawa (Journal of Fish Biology, 2016)
A laboratory experiment was conducted by varying the undersurface area of nesting substratum and the number of females in an experimental tank to elucidate the determinants of the mating pattern in the stream goby, Rhinogobius sp. cross‐band type. Males with larger nests tended to attract two or more females to their nest in a tank. Moreover, males spawned simultaneously with multiple females and entire brood cannibalism by males was rarely observed under a female‐biased sex ratio. When males spawned with a single female with low fecundity, however, entire brood cannibalism occurred at a high frequency, suggesting that a male guarding a nest with fewer eggs consumes the brood. Therefore, spawning behaviour of females that leads to a large egg mass would decrease the risk of entire brood cannibalism. In this species, simultaneous spawning by multiple females in a nest serves as a female counter‐measure against entire brood cannibalism. These results suggest that a conflict of interest between the sexes through brood cannibalism is a major determinant of simultaneous spawning.

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

The importance of primary inoculum and area-wide disease management to crop health and food security - A. Bergamin Filho; A. K. Inoue-Nagata; R. B. Bassanezi; J. Belasque; L. Amorim; M. A. Macedo; J. C. Barbosa; L. Willocquet; S. Savary (Food Security, 2016)

Past climate change drives current genetic structure of an endangered freshwater mussel species - Kentaro Inoue; Brian K. Lang; David J. Berg (Molecular Ecology, 2015)
Historical‐to‐recent climate change and anthropogenic disturbance affect species distributions and genetic structure. The Rio Grande watershed of the United States and Mexico encompasses ecosystems that are intensively exploited, resulting in substantial degradation of aquatic habitats. While significant anthropogenic disturbances in the Rio Grande are recent, inhospitable conditions for freshwater organisms likely existed prior to such disturbances. A combination of anthropogenic and past climate factors may contribute to current distributions of aquatic fauna in the Rio Grande basin. We used mitochondrial DNA and 18 microsatellite loci to infer evolutionary history and genetic structure of an endangered freshwater mussel, P openaias popeii , throughout the Rio Grande drainage. We estimated spatial connectivity and gene flow across extant populations of P . popeii and used ecological niche models ( ENM s) and approximate B ayesian computation ( ABC ) to infer its evolutionary history during the Pleistocene. structure results recovered regional and local population clusters in the Rio Grande. ENM s predicted drastic reductions in suitable habitat during the last glacial maximum. ABC analyses suggested that regional population structure likely arose in this species during the mid‐to‐late Pleistocene and was followed by a late Pleistocene population bottleneck in New Mexico populations. The local population structure arose relatively recently, perhaps due to anthropogenic factors. P openaias popeii , one of the few freshwater mussel species native to the Rio Grande basin, is a case study for understanding how both geological and anthropogenic factors shape current population genetic structure. Conservation strategies for this species should account for the fragmented nature of contemporary populations.

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Identification and characterization of 12 microsatellite loci for Physa in the Chihuahuan Desert - Kofi N. Ansah; Kentaro Inoue; Brian K. Lang; David J. Berg (Conservation Genetics Resources, 2014)

A measure of genetic diversity of goldenseal (Hydrastis canadensis L.) by RAPD analysis - Maiko Inoue; Kerry J. Kelley; Amy Frary; Lyle E. Craker (Genetic Resources and Crop Evolution, 2013)

Development and characterization of 20 polymorphic microsatellite markers for the Texas hornshell, Popenaias popeii (Bivalvia: Unionidae), through next-generation sequencing - Kentaro Inoue; Brian K. Lang; David J. Berg (Conservation Genetics Resources, 2013)

Soybean chlorotic spot virus, a novel begomovirus infecting soybean in Brazil - Daniela Coco; Iara P. Calil; Otavio J. B. Brustolini; Anesia A. Santos; Alice K. Inoue-Nagata; Elizabeth P. B. Fontes (Archives of Virology, 2013)

Molecular and biological characterization of a new Brazilian begomovirus, euphorbia yellow mosaic virus (EuYMV), infecting Euphorbia heterophylla plants - Fernanda R. Fernandes; Leonardo C. Albuquerque; Cristiane L. de Oliveira; Andréa R. R. Cruz; Wesley B. da Rocha; Talita G. Pereira; Fernanda Y. B. Naito; Natália de M. Dias; Tatsuya Nagata; Josias C. Faria; Francisco M. Zerbini; Francisco J. L. Aragão; et al. (Archives of Virology, 2011)

Isolation and characterization of 17 polymorphic microsatellite loci in the spectaclecase, Cumberlandia monodonta (Bivalvia: Margaritiferidae) - Kentaro Inoue; Gregory R. Moyer; Ashantyé Williams; Emy M. Monroe; David J. Berg (Conservation Genetics Resources, 2011)

Colony growth and reproductive ability of feral nests of the introduced bumblebee Bombus terrestris in northern Japan - M. N. Inoue; J. Yokoyama; K. Tsuchida (Insectes Sociaux, 2010)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Reflectance characteristics of major land surfaces in slash‐and‐burn ecosystems in Laos - Y. Inoue; J. Qi; A. Olioso; Y. Kiyono; T. Horie; H. Asai; K. Saito; Y. Ochiai; T. Shiraiwa; L. Douangsavanh (International Journal of Remote Sensing, 2008)

Traceability of slash‐and‐burn land‐use history using optical satellite sensor imagery: a basis for chronosequential assessment of ecosystem carbon stock in Laos - Y. Inoue; J. Qi; A. Olioso; Y. Kiyono; T. Horie; H. Asai; K. Saito; Y. Ochiai; T. Shiraiwa; L. Douangsavanh (International Journal of Remote Sensing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Cospeciation in the triplex symbiosis of termite gut protists ( Pseudotrichonympha spp.), their hosts, and their bacterial endosymbionts - S. NODA; O. KITADE; T. INOUE; M. KAWAI; M. KANUKA; K. HIROSHIMA; Y. HONGOH; R. CONSTANTINO; V. UYS; J. ZHONG; T. KUDO; M. OHKUMA (Molecular Ecology, 2007)
A number of cophylogenetic relationships between two organisms namely a host and a symbiont or parasite have been studied to date; however, organismal interactions in nature usually involve multiple members. Here, we investigated the cospeciation of a triplex symbiotic system comprising a hierarchy of three organisms — termites of the family Rhinotermitidae, cellulolytic protists of the genus Pseudotrichonympha in the guts of these termites, and intracellular bacterial symbionts of the protists. The molecular phylogeny was inferred based on two mitochondrial genes for the termites and nuclear small‐subunit rRNA genes for the protists and their endosymbionts, and these were compared. Although intestinal microorganisms are generally considered to have looser associations with the host than intracellular symbionts, the Pseudotrichonympha protists showed almost complete codivergence with the host termites, probably due to strict transmissions by proctodeal trophallaxis or coprophagy based on the social behaviour of the termites. Except for one case, the endosymbiotic bacteria of the protists formed a monophyletic lineage in the order Bacteroidales, and the branching pattern was almost identical to those of the protists and the termites. However, some non‐codivergent evolutionary events were evident. The members of this triplex symbiotic system appear to have cospeciated during their evolution with minor exceptions; the evolutionary relationships were probably established by termite sociality and the complex microbial community in the gut.

Fluctuating serotonergic function in premenstrual dysphoric disorder and premenstrual syndrome: findings from neuroendocrine challenge tests - Y. Inoue; T. Terao; N. Iwata; K. Okamoto; H. Kojima; T. Okamoto; R. Yoshimura; J. Nakamura (Psychopharmacology, 2006)

Synchrotron IR study of hydrous ringwoodite (γ-Mg2SiO4) up to 30 GPa - E. M. Chamorro Pérez; I. Daniel; J.-C. Chervin; P. Dumas; J. D. Bass; T. Inoue (Physics and Chemistry of Minerals, 2006)

Role of hepatocyte nuclear factor 4α in control of blood coagulation factor gene expression - Yusuke Inoue; L. Luanne Peters; Sun Hee Yim; Junko Inoue; Frank J. Gonzalez (Journal of Molecular Medicine, 2006)

Role of hepatocyte nuclear factor 4α in control of blood coagulation factor gene expression - Yusuke Inoue; Luanne L. Peters; Sun Hee Yim; Junko Inoue; Frank J. Gonzalez (Journal of Molecular Medicine, 2006)

The phase boundary between wadsleyite and ringwoodite in Mg2SiO4 determined by in situ X-ray diffraction - T. Inoue; T. Irifune; Y. Higo; T. Sanehira; Y. Sueda; A. Yamada; T. Shinmei; D. Yamazaki; J. Ando; K. Funakoshi; W. Utsumi (Physics and Chemistry of Minerals, 2006)

Assessment of room temperature influence on finger blood flow response induced by short-term grasping of vibrating handle - M. H. Mahbub; M. Inoue; K. Yokoyama; M. S. Laskar; H. Ohnari; K. Suizu; J. Inagaki; Y. Takahashi; N. Harada (International Archives of Occupational and Environmental Health, 2006)

High prevalence of hepatitis B, C and delta virus infections among blood donors in Mongolia - B. Tsatsralt-Od; M. Takahashi; T. Nishizawa; J. Inoue; D. Ulaankhuu; H. Okamoto (Archives of Virology, 2005)

Effect of room temperature on percentage finger systolic blood pressure response to finger cooling - M. S. Laskar; K. Ohmura; M. Inoue; K. Yokoyama; J. Inagaki; Y. Takahashi; M. H. Mahbub; H. Ohnari; N. Harada (European Journal of Applied Physiology, 2005)

Sundasalanx (Sundasalangidae) is a progenetic clupeiform, not a closely‐related group of salangids (Osmeriformes): mitogenomic evidence - N. B. Ishiguro; M. Miya; J. G. Inoue; M. Nishida (Journal of Fish Biology, 2005)
Partitioned Bayesian analysis of whole mitochondrial genome sequences from 30 basal teleosts confidently placed Sundasalanx (Sundasalangidae) within the Clupeiformes, not Osmeriformes as originally thought. This study represents the first demonstration of the phylogenetic position of Sundasalanx on a phylogenetic tree.

A novel melon flexivirus transmitted by whitefly - T. Nagata; D. M. T. Alves; A. K. Inoue-Nagata; T.-Y. Tian; E. W. Kitajima; J. E. Cardoso; A. C. de vila (Archives of Virology, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Walking velocity measured over 5 m as a basis of exercise prescription for the elderly: preliminary data from the Nakanojo Study - Yukitoshi Aoyagi; Fumiharu Togo; Shigemura Matsuki; Yasuhito Kumazaki; Shigeru Inoue; Tomoko Takamiya; Mamiko Naka; Roy J. Shephard (European Journal of Applied Physiology, 2004)

Ecological Aspects of the Downstream Migration of Introduced European Eels in the Uono River, Japan - Takeshi Miyai; Jun Aoyama; Seji Sasai; Jun G. Inoue; Michael J. Miller; Katsumi Tsukamoto (Environmental Biology of Fishes, 2004)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Oculomotor sequence learning: a positron emission tomography study - R. Kawashima; J. Tanji; K. Okada; Motoaki Sugiura; Kazunori Sato; Shigeo Kinomura; Kentaro Inoue; Akira Ogawa; Hiroshi Fukuda (Experimental Brain Research, 1998)

Viruses produced from complementary DNA of virulent and avirulent strains of swine vesicular disease viruses retain the in vivo and in vitro characteristics of the parental strain - T. Kanno; T. Inoue; D. Mackay; P. Kitching; S. Yamaguchi; J. Shirai (Archives of Virology, 1998)

Genetic studies of the leptin receptor gene in morbidly obese French Caucasian families - Stephan Francke; Karine Clement; Christian Dina; Hiroshi Inoue; Philip Behn; Vincent Vatin; Arnaud Basdevant; Bernard Guy-Grand; M. Alan Permutt; Philippe Froguel; J. Hager (Human Genetics, 1997)

Physical and genetic maps of the human herpesvirus 7 strain SB genome - G. Dominguez; J. B. Black; F. R. Stamey; N. Inoue; P. E. Pellett (Archives of Virology, 1996)

Restriction endonuclease mapping and molecular cloning of the human herpesvirus 6 variant B strain Z29 genome - G. J. Lindquester; N. Inoue; R. D. Allen; J. W. Castelli; F. R. Stamey; T. R. Dambaugh; J. J. O'Brian; R. M. Danovich; N. Frenkel; P. E. Pellett (Archives of Virology, 1996)

Identification of epitopes associated with different biological activities on the glycoprotein of vesicular stomatitis virus by use of monoclonal antibodies - S. Nagata; Y. Okamoto; T. Inoue; Y. Ueno; T. Kurata; J. Chiba (Archives of Virology, 1992)